2018
DOI: 10.1177/1742715018808905
|View full text |Cite
|
Sign up to set email alerts
|

The power of positioning: How leadership work unfolds in team interactions

Abstract: Drawing on literature conceptualising leadership as a discursive accomplishment, this paper defines leadership as leadership work: a process unfolding through talk, and depending on a unique dynamic among the resources that participants bring to an interaction, and the ability of the participants to creatively mobilise these resources to perform the task at hand. Leadership work can be understood through the analysis of how individuals position themselves and others in an interaction. Data from an ethnographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 64 publications
(149 reference statements)
1
21
0
Order By: Relevance
“…In particular, our analysis suggests the importance of taking close account of the leadership work that takes place prior to decision making as it can influence the decisions that are ultimately made. However, this work may not be accounted for in studies that rely on surveys and interviews (Meschitti, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, our analysis suggests the importance of taking close account of the leadership work that takes place prior to decision making as it can influence the decisions that are ultimately made. However, this work may not be accounted for in studies that rely on surveys and interviews (Meschitti, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lingard et al (2012) showed how physicians, who are traditionally seen at the apex of the professional hierarchy, can make efforts to encourage collective leadership by using inclusive language such as the pronoun "we," by considering the pertinence of different expertise to case discussions, and by using team members' first names; however, decision making ultimately remained in physicians' hands. The use of these interactional strategies is influenced by the emergent and structural interactional resources (Meschitti, 2019) on which members may draw, for instance humor, one's position in the hierarchy, or a claim to expert knowledge.…”
Section: Sharing Leadership Interprofessional Teams and Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…Through close analysis of interactional data, Van de Mieroop et al 2020show that leadership is negotiated in subtle ways through talk, gaze, the use of space, artifacts, and so on. Further, although not studying objects as such, Meschitti (2019) argues that "(i)ndexicality and the negotiation around objects (such as the formula on the board) are also central in leadership work" (p. 17). Outside of the field of leadership, however, studies have demonstrated the relevance of focusing on objects in terms of understanding social phenomena such as sensemaking (Mondada, 2011), coordination (LeBaron et al, 2016, or strategizing (Samra-Fredericks, 2010).…”
Section: Materiality and Objectsmentioning
confidence: 99%